Teori Belajar: Humanistik dan Konstruktivistik dalam Perspektif Psikologi Barat dan Islam - Nesa Novrizal; Rahman, Imas Kania; Andriana, Nesia (Indonesian Journal Publisher, 2023)
Learning theory is an important foundation in the process of education and effective learning. The two main theories that play a role in it are humanistic and constructivist learning theories. However, in reality, there are still many educators in the learning process in the classroom who use methods that tend to only focus on reward and punishment and there is also no active involvement of students. So that the impact on the cognitive development of students becomes slow. The aims of this study: 1) to analyze humanistic learning theory, 2) to analyze constructivist learning theory, 3) to analyze humanistic and constructivist learning theory in an Islamic perspective. The literature review was used by researchers in this study using documentary techniques as data analysis techniques. The results of the study explain that in the learning process the methods used by educators must be varied, so as to help students develop their knowledge and focus on humanizing students so that students do not only receive rewards or punishments.